The Influence of Knowledge, Religiosity, and Promotion through Social Media on the Digital Cash Waqf Students Intention - Lutfiyah, Elya Diyanatu; Berakon, Izra; Mansyur, Rizkia Amania (SMART Insight, 2025)
This study aims to analyze the influence of knowledge, religiosity, promotion through social media, and the level of trust of waqf institutions on the intention of students to waqf money digitally. This study also analyzes the influence of knowledge, religiosity, and promotion through social media on students' intentions to do waqf money digitally by mediating the level of trust of waqf institutions. The sampling techniques in this study are non-probability sampling, and the type of sample used in this study is purposive sampling, and the determination of the number of samples in this study is based on the Hinkin (1995), 110 samples were obtained. The analysis technique was carried out by PLS-SEM analysis with testing Outer model and Inner model Using Software SmartPLS 3.0. The results of this study were obtained that the variables of knowledge, religiosity, promotion through social media, and the level of trust of waqf institutions had a positive and significant effect on the intention of students to waqf money digitally. In addition, the variable level of trust of waqf institutions partially mediates the influence of the variables of knowledge, religiosity, and promotion through social media on the intention of students to do waqf money digitally.